Pemberdayaan Karang Taruna Kampung Wisata Seribu Bunga Nglurah Kecamatan Tawangmangu dengan Pembuatan Pupuk Kompos Berbahan Daun Kaliandra - Agus Choirul Arifin Arifin; Yoga Ahdiat Fakhrudi; Farid Majedi; Achmad Aminudin; Noorsakti Wahyudi; Nana Ainiya Khalidah (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2023)
Nglurah Hamlet is known as the “Kampung Sewu Kembang”. This hamlet is famous as a hamlet producing ornamental plants / flowers that supply various kinds of plants to the Karanganyar area to outside Java. Around Dusun Nglurah there are abundant calliandra plants which are usually used by local residents for raw materials for making fertilizers as fertilizer for ornamental plants. However, the use of calliandra fertilizer is limited to household use, it has not been mass produced and the manufacturing process is still simple. By providing training solutions to the community members of the Nglurah hamlet in the form of life skills, in the form of training in making compost made from calliandra which can be used as a provision for the skills of residents, especially youth groups in the world of work and entrepreneurship, and are ready to compete in the competition in the world of work. Implementation of Community Partnership Program (PKM) activities in Mitra 1, the target solution provided using a training method with a model for delivering material on the theory of the composting process, the practice of making compost and packaging to facilitate sales